2021
DOI: 10.1021/acs.energyfuels.0c04046
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Metal Elements in Biomass Pyrolysis: A Review

Abstract: One of the main drawbacks of using biomass as pyrolysis feedstock consists of the huge variability of the different biomass resources which undermines the viability of downstream processes. Inherent inorganic elements greatly contribute to enhance the compositional variability issues due to their catalytic effect (especially alkali and alkaline earth metals (AAEMs)) and the technical problems arising due to their presence. Due to the different pretreatments adopted in the experimental investigations as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 377 publications
1
34
0
Order By: Relevance
“…With the addition of NaCl in the blend, Na metal also increases in the sample. Thus, it was observed a reduction of the available catalytic pores in biomass that collapse reverting the formation of silica compounds 32 . The results demonstrated that Si compounds vanished after adding salt, showing that NaCl promotes ring‐opening / closing, isomerization, decarboxylation, and dehydration reactions, after which these structures disappeared to form cyclic hydrocarbons, and alkanes, leaving silica molecules as a residue.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…With the addition of NaCl in the blend, Na metal also increases in the sample. Thus, it was observed a reduction of the available catalytic pores in biomass that collapse reverting the formation of silica compounds 32 . The results demonstrated that Si compounds vanished after adding salt, showing that NaCl promotes ring‐opening / closing, isomerization, decarboxylation, and dehydration reactions, after which these structures disappeared to form cyclic hydrocarbons, and alkanes, leaving silica molecules as a residue.…”
Section: Resultsmentioning
confidence: 95%
“…It is noticeable that silicon was abundant metal in PS sample (0.28 wt%). This metalloid was excluded from the mineral biomass matter because it could be derived from soil contamination 32 . According to Vassilev et al ., the presence of inorganic elements belonging from biomass collection, transportation or transformation, defined as technogenic minerals, cannot be considered inherent metals 33 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of Biochar degradation is 274 °C, higher than that of Biochar@Ag which starts to degrade at 200 °C, well below the bare Biochar. This could be due to catalytic thermal degradation of the carbonized matter by silver NPs [22]. Degradation progresses until 377 °C and the mass becomes stable.…”
Section: Physicochemical Properties Of Biochar and Biochar@agmentioning
confidence: 99%
“…Alkaline and alkaline earth metal ions (AAEMs) are part of the plant's nutrient to enable the plant to grow [15,126]. Lignocellulose is comprised of four different types of materials: lignin, cellulose, hemicellulose, and inorganics.…”
Section: Catalyst Deactivationmentioning
confidence: 99%